2014
DOI: 10.3109/10428194.2014.907893
|View full text |Cite
|
Sign up to set email alerts
|

Ectonucleoside triphosphate diphosphohydrolase-1 (E-NTPDase1/CD39) as a new prognostic marker in chronic lymphocytic leukemia

Abstract: Numerous prognostic markers were introduced to screen for patients with B-cell chronic lymphocytic leukemia (B-CLL) likely to have a progressive course, bearing the potential to facilitate risk-adapted treatment strategies. Extracellular adenosine triphosphate (ATP) functions as a "natural adjuvant" that boosts immune response in the tumor microenvironment. Ectonucleoside triphosphate diphosphohydrolase-1 (CD39/ENTPD1) is the ectonucleotidase that catalyzes the hydrolysis of ATP. The present study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Thus, the adenosine accumulation around leukemic cells that is induced by the high CD39 expression is further enhanced by the lack of CD26, which actively suppresses the cell immunity surrounding ATLL cells, producing a favorable environment for their survival. Recently, some papers reported that in chronic lymphocytic leukemia (CLL) patients, CD39-expressing nonmalignant T lymphocytes are increased compared with in normal control, and the higher expression levels of CD39 are associated with the worse prognosis of the disease [16,36]. This information would support our results that CD39 expression on ATLL cells themselves correlates with the progression of disease through the suppression of tumor immune in the host.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the adenosine accumulation around leukemic cells that is induced by the high CD39 expression is further enhanced by the lack of CD26, which actively suppresses the cell immunity surrounding ATLL cells, producing a favorable environment for their survival. Recently, some papers reported that in chronic lymphocytic leukemia (CLL) patients, CD39-expressing nonmalignant T lymphocytes are increased compared with in normal control, and the higher expression levels of CD39 are associated with the worse prognosis of the disease [16,36]. This information would support our results that CD39 expression on ATLL cells themselves correlates with the progression of disease through the suppression of tumor immune in the host.…”
Section: Discussionsupporting
confidence: 87%
“…22 It was recently published that combinations of antibodies against CD39 and CD73 reduced the growth of different mouse tumors. 23 CD39 is found in cancers such as chronic lymphocytic leukemia 24 and subgroups of gastric cancers, 25 which makes these cancers targets for anti-CD39 antibodies and inhibitors. Although CD39 is not expressed by healthy PC, 26 we found that a large proportion of MM patients expressed CD39 on their myeloma cells.…”
Section: Open Accessmentioning
confidence: 99%
“…Indeed, CD39 was reported: (i) to inversely correlate with disease stage, being expressed at higher levels in stage 0–2 CLLs compared to stages 3–4 and (ii) with therapy requirement, being higher in treatment-naïve patients. In addition, expression of CD39 is enriched in samples carrying mutated IGHV genes, a common feature in good prognosis CLL subset [ 53 , 54 ]. Accordingly, CD39 ATPase and ADPase activities are enhanced in stage 0–2 CLL than in stage 3–4 [ 55 ].…”
Section: Expression Of the Adenosinergic Axis Machinery On Cll Celmentioning
confidence: 99%
“…Consistently, CD39 + T lymphocytes are enriched in CLL patients that need to be treated, compared to untreated patients [ 56 , 57 ]. Ultimately, T-cell CD39 expression is considered predictive of treatment requirement, as a significantly shorter time to first treatment (TTFT) was observed in patients with CD39 high T cells compared to CD39 low [ 54 ].…”
Section: Expression Of the Adenosinergic Axis Machinery On Cll Celmentioning
confidence: 99%